« Ever step you take is forever » : fin de l’héroïsme et vacuité spirituelle dans No Country for Old Men - Martin Berny (Revue LISA)
Joel and Ethan Coen’s take on No Country for Old Men can be seen as even darker and more pessimistic than the text it stems from. Addressing more directly two of their favorite themes, namely existential misplacement and the end of heroism, they bring a certain skepticism to their film. As a philosophical step orchestrated by the Coens, what seems to be missing or elided from the novel by Cormac McCarthy elicits a tumble into chaos. This article will demonstrate that this film adaptation makes room for a negative space that brings out a form of spiritual emptiness already found in McCarthy’s book. We will see that more specifically through recurring motifs in the Coens’ canon and threshold images deployed throughout the film, which allow the audience to engage and provide a meaning to the work that remains ambiguous and open to interpretation.